Retrospective investigation of porcine circoviruses in cases of porcine dermatitis and nephropathy syndrome - Àlex Cobos; Mariano Domingo; Mónica Pérez; Eva Huerta; Anna Llorens; Joaquim Segalés; Marina Sibila (Veterinary Research)
Abstract Porcine dermatitis and nephropathy syndrome (PDNS) is a severe condition that affects mainly growing pigs and is considered to be caused by a type III hypersensitivity reaction. Although porcine circovirus 2 (PCV-2) is the antigen linked to this condition, porcine circovirus 3 (PCV-3) has also been proposed to be causally associated with PDNS. Moreover, the initial description of porcine circovirus 4 (PCV-4) also related this novel agent to this clinicopathological entity. Therefore, this retrospective study included a large number of PDNS cases (n = 102) fulfilling specific histologic criteria in search of known porcine circoviruses (PCV-1 to PCV-4) by conventional and/or quantitative PCR (qPCR). All the samples were subjected to PCV-2 immunohistochemistry (IHC) or conventional in situ hybridization (C-ISH), and RNAscope® (R-ISH) was used to study PCV-2 and PCV-3 localization in a subset of the samples. All PDNS cases were PCV-2 positive by qPCR, while 30 of them (29.4%) yielded PCV-3 qPCR positivity; PCV-2 viral loads were significantly greater than PCV-3 viral loads. All animals were negative for PCV-1 and PCV-4. By C-ISH/IHC, 63 cases (61.8%) were positive for PCV-2, with low to moderate amounts of antigen. R-ISH demonstrated higher sensitivity, as all studied cases were positive; however, neither PCV-2 nor PCV-3 were consistently found within characteristic PDNS lesions. These results indicate that all PDNS-affected pigs were infected with PCV-2, emphasizing the likelihood that this viral antigen is causally linked to this condition. In contrast, no evidence of the association of PCV-1, PCV-3 or PCV-4 with PDNS was found.